Unpacking the dynamics: The influence of M&A networks on e-innovation in African Listed Firms - Suleman Bawa; Xie Yongping; Ibn W. Benin; Inuusah Mahama; Abdulaziz S. Almudaihesh (South African Journal of Business Management)
Purpose: This study examines the impact of mergers and acquisitions (MA) networks on e-innovation networks within African-listed firms. It provides empirical evidence of how MA influences e-innovation, emphasising the roles of resource acquisition and market dynamics in promoting innovation, technological advancement, and economic growth.